Pengaruh Gaya Komunikasi Guru Dan Kontrol Orang Tua Terhadap Performa Akademik Siswa Kelas XII IPS SMA Negeri 1 Dumoga - Kemur, Stevan; Johny Taroreh; Allen CH Manongko (Indo Publishing, 2025)
This study aims to examine the influence of teachers' communication style (X1) and parental control (X2) on students' academic performance (Y) in Economics subject among 43 twelfth-grade social science students at SMA Negeri 1 Dumoga during the 2022/2023 academic year. A quantitative approach was employed using multiple linear regression analysis with SPSS 26. The entire population of 43 students was used as the full sample through census sampling. Primary data were collected from a 1-5 Likert scale questionnaire (Y: 8 items on Economics performance, X1: 15 items on teachers' communication style, X2: 9 items on parental control). Classical assumption tests (normality, multicollinearity, heteroscedasticity, autocorrelation) were conducted prior to regression (model: Y = β0 + β1 X1 + β2 X2 + e). The simultaneous influence of X1 and X2 was significant (F=27.231 >4.085, Sig.<0.001; R²=0.577 or 57.7%). Partially, both were positive and significant (β1=0.76 for X1, β2=0.84 for X2; Sig t<0.05). Assumptions were met, and the model was valid. Teachers' communication style and parental control have a positive and significant influence on students' academic performance, with a total contribution of 57.7%—emphasizing the synergy of effective teacher-student interactions and parental supervision to enhance learning outcomes in rural areas.